2011
DOI: 10.3892/or.2010.1089
|View full text |Cite
|
Sign up to set email alerts
|

Methyl-CpG binding protein MBD2 is implicated in methylation-mediated suppression of miR-373 in hilar cholangiocarcinoma

Abstract: Abstract. Aberrant expression of miRNAs is associated with particular cancers showing tissue-and clinical-featurespecificity patterns. Some miRNA genes harboring or being embedded in CpG islands undergo methylation mediated silencing. MBP, methyl CpG binding protein, suppresses transcription through binding to methylated CpG dinucleotides. Expression of miR-373 has been reported to be suppressed in malignant bile duct cell lines. Bioinformatic prediction reveals that the transcription start site (TSS) of miR-3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 36 publications
1
18
0
Order By: Relevance
“…The increasing of the miR-129-5p expression was related to antitumor activity of TSA, whereas the inactivation of miR-129-5p significantly blocked the TSA-induced cell death. Chen et al pointed out that miR-373 was reactivated by the pharmacologic induction of TSA26. Zhang et al evaluated the effect of TSA to miRNA expression in BxPC-3 human cancer cell27.…”
Section: Resultsmentioning
confidence: 99%
“…The increasing of the miR-129-5p expression was related to antitumor activity of TSA, whereas the inactivation of miR-129-5p significantly blocked the TSA-induced cell death. Chen et al pointed out that miR-373 was reactivated by the pharmacologic induction of TSA26. Zhang et al evaluated the effect of TSA to miRNA expression in BxPC-3 human cancer cell27.…”
Section: Resultsmentioning
confidence: 99%
“…All these compounds interact with each other, and miRNAs are regulated by the other parts of this network. One crucial aspect in this context seems to be the interaction of miRNAs with DNA methylation, which has been described to control and "fine tune" various miRNAs by epigenetic inactivation due to aberrant hypermethylation [20][21][22][23][24][25][26][27]. Most interestingly, DNA methylation has been proven to play an important role in drug resistance, and there is effort to assess "DNA methylationtargeted" therapy with drugs such as DNA methyltransferase inhibitors (e.g., decitabine) as potential weapon against cancer [28][29][30][31].…”
Section: Mirna Biogenesis and Regulationmentioning
confidence: 98%
“…In this context, Chen et al described MBD2 as a direct target of miRNA-373, a tumor miRNA species downregulated in hilar CC, which was associated with advanced clinical stage [63]. MBD2 is involved in the DNA methylation-dependent repression of gene transcription as a reader of cytosine methylation and was suggested as a marker associated with poor prognosis for patients with hepatocellular carcinoma [64, 65].…”
Section: Microrna and Btcmentioning
confidence: 99%
“…DNA methylation at CpG islands in promoter regions is an epigenetic mechanism that leads to transcriptional repression of the respective gene. Chen et al observed downregulation of miRNA-373 in patients with hilar cholangiocarcinoma [63]. In order to investigate the mechanism of the miRNA-373 deregulation, they analyzed the genomic surrounding of the miRNA-373 gene and identified a region at the 5′ flank that may serve as a promoter.…”
Section: Microrna and Btcmentioning
confidence: 99%